A new Muscarella from Tapanti National Park, Costa Rica - Fernández Campos, Melania (2021)
A new species of Muscarella from Costa Rica, is described and illustrated. Muscarella tapantiensis most resembles M. coeloglossa but differs in the longer pedicels (3-5 vs. 1-2 mm), the shorter (2.5-2.8 vs. 3.75 mm), connate (vs. free) lateral sepals, and the lip with triangular (vs. broadly rounded) lower lateral lobes. Muscarella xanthella also resembles M. tapantiensis; however, it differs in the successively flowered raceme with alternate pedicels, the deeply fimbriate petals and the thick, rounded lip with densely verrucose lateral lobes. We provide illustrations, etymology, notes on ecology, pictures of the plants and habitat, and a distribution map of the new species. We discuss the inclusion of this species in the genus Muscarella.